Life experiences and coping mechanisms among breast cancer patients in an urban Malaysian hospital a qualitative study - Nour Hanan Daniah MB,; Ahmad Anwaar MS,; Siti Soraya AR,; Zarini Ismail (Penerbit UKM, 2024)
Indexed by WOS/MYCITE